2012
DOI: 10.1007/s00264-012-1732-1
|View full text |Cite
|
Sign up to set email alerts
|

Frontal plane alignment after total knee arthroplasty using patient-specific instruments

Abstract: Purpose Although total knee arthroplasty (TKA) is regularly associated with favorable outcomes, considerable research efforts are still underway to improve its ability to achieve a neutral postoperative mechanical axis. Patientspecific instrumentation (PSI) was introduced with this and other goals in mind. The current retrospective study was designed to determine whether PSI would lead to a hipknee-ankle angle (HKA) within ±3°of the ideal alignment of 180°. Methods A long-leg x-ray of the knee was performed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 24 publications
(37 reference statements)
8
60
0
2
Order By: Relevance
“…As this is an update of an earlier study [12], in which data from 50 additional patients were available, these results also reconfirm the earlier conclusion that this specific technology is effective in addressing the issue of malalignment. Further follow-up will be needed to ascertain the long-term impact of these findings.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…As this is an update of an earlier study [12], in which data from 50 additional patients were available, these results also reconfirm the earlier conclusion that this specific technology is effective in addressing the issue of malalignment. Further follow-up will be needed to ascertain the long-term impact of these findings.…”
Section: Discussionsupporting
confidence: 85%
“…By using pre-operative MRI data and full-length anterior/posterior radiographs to ascertain the current and planned mechanical axis, engineers are able to produce tibial and femoral resection guides fitted to the patient's specific anatomy. This is the latest study to support the accuracy of this technology [12,18,31]. It also represents an update of an earlier analysis in which results for a smaller cohort (100 knees) operated with this technology were presented without a comparison cohort [12].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…2 Determination of the zone of mechanical axis (ZMA), i.e. the zone of the tibial base plate (divided into three equal regions) that intersect with the mechanical axis of the limb [24]; intersection with zones II-V was considered an outlier et al [31], who found no statistically significant differences between MRI-based Signature PSI and traditional instrumentation in terms of obtaining a neutral mechanical axis and individual component alignment in the frontal plane. Nunley et al [8] compared coronal alignment measurements after TKA performed using traditional instrumentation and two different types of custom-made guides: Signature™ MRIbased PSI, and OtisMed™ MRI-based PSI (manufactured to restore kinematic alignment).…”
Section: Discussionmentioning
confidence: 99%